2023
DOI: 10.1101/2023.01.03.522681
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of a new antiphage system inMycobacteriumphage Butters

Abstract: During lysogeny temperate phages establish a truce with the bacterial host. In this state, the phage genome (prophage) is maintained within the host environment. Consequently, many prophages have evolved systems to protect the host from heterotypic viral attack. This phenomenon of prophages mediating defense of their host against competitor phages is widespread among temperate mycobacteriophages. We previously showed that theMycobacteriumphage Butters prophage encodes a two-component system (gp30/31) that inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Indeed, we found that the 6 defense systems that were previously reported as the most prophage-encoded in all prokaryotic genomes (above 60% of the total number of systems) 16 were almost exclusively found in Proteobacteria (99% of the occurrences of these 6 systems). A handful of systems were recently discovered in Mycobacterium phages [45][46][47][48] , which are by far the most characterized and studied actinobacterial phages 49 . Only one of these systems, gp29-gp30, is currently detected by DefenseFinder, and it is exclusively found in Actinobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, we found that the 6 defense systems that were previously reported as the most prophage-encoded in all prokaryotic genomes (above 60% of the total number of systems) 16 were almost exclusively found in Proteobacteria (99% of the occurrences of these 6 systems). A handful of systems were recently discovered in Mycobacterium phages [45][46][47][48] , which are by far the most characterized and studied actinobacterial phages 49 . Only one of these systems, gp29-gp30, is currently detected by DefenseFinder, and it is exclusively found in Actinobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The genome DNA of K4JX5 Phage was extracted using the phenol‐chloroform method as described earlier 53 . A total of 200 ng of the genomic DNA was electroporated into M. smegmatis strains and supplemented with 900 μl 7H9 medium, followed by shaking at 160 rpm at 37°C for 1 h. The cells were collected, re‐suspended with 200 μl of 7H9 medium, and then mixed with 1 ml of the wild‐type M. smegmatis strain and 5 ml of LB‐agar medium.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, we found that the six defence systems that were previously reported as the most prophage-encoded in all prokaryotic genomes (above 60 % of the total number of systems) [19] were almost exclusively found in Proteobacteria (99 % of the occurrences of these six systems). A handful of systems were recently discovered in Mycobacterium phages [52,[55][56][57], which are by far the most characterized and studied actinobacterial phages [58]. Only one of these systems, gp29-gp30, is currently detected by DefenseFinder, it is exclusively found in Actinobacteria.…”
Section: Discovery Bias: More Systems To Discover In Actinobacteria A...mentioning
confidence: 99%